2018
DOI: 10.1001/jamasurg.2018.0215
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Bariatric Surgery With Changes in Interpersonal Relationship Status

Abstract: In addition to its association with obesity comorbidities, bariatric surgery-induced weight loss is also associated with changes in relationship status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 33 publications
5
47
2
Order By: Relevance
“…For example, prioritising friendships which accommodate patient's post-surgery lifestyles by changing socialising from food-centred to activity-based pursuits [26]. A recent large-scale, quantitative study has also reported frequent changes to marital relationships status following bariatric surgery including both dissolution of existing relationships and entering new ones, which could have implications for availability and levels of received social support [39]. Lastly, due to small sample size and incomplete clinical records, the measure of ethnicity used here was crude and precluded analyses in specific ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…For example, prioritising friendships which accommodate patient's post-surgery lifestyles by changing socialising from food-centred to activity-based pursuits [26]. A recent large-scale, quantitative study has also reported frequent changes to marital relationships status following bariatric surgery including both dissolution of existing relationships and entering new ones, which could have implications for availability and levels of received social support [39]. Lastly, due to small sample size and incomplete clinical records, the measure of ethnicity used here was crude and precluded analyses in specific ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…One possible mechanism may be that intensive preoperative MDT interventions do not deliver behavioural skills that are relevant in the post‐operative phase. Post‐operative behavioural interventions are specialized to meet the unique side effects and symptoms of bariatric surgery, such as dietary portion control, different dietary priorities, managing hydration, changing cognitive states, changing demographic, and relationship characteristics that are triggered by the surgery, or managing physical activity whilst experiencing symptoms such as nausea or faintness . Other possible contributors are psychosocial factors such as the stage of readiness to change and body image, as well as facilitators and barriers that may vary preoperatively and post‐operatively …”
Section: Discussionmentioning
confidence: 99%
“…Many researchers use LISA for medical research [ 1 32 ], when retrieving data on education [ 40 49 ], income [ 40 , 50 52 ] (including family income [ 53 , 54 ]), civil status [ 40 , 42 ], unemployment [ 50 , 52 , 55 57 ], and work disability benefits [ 1 , 50 , 58 ] in association with many diseases and disorders. LISA data can be used to compare responders and non-responders in questionnaire studies.…”
Section: Contents Of Lisamentioning
confidence: 99%